The complex influence of external and internal electricity networks on the magnetic field level in residential premises of buildings - Rozov, V. Yu.; Pelevin, D. Ye.; Reutskiy, S. Yu.; Kundius, K. D.; Vorushylo, A. O. (Національний технічний університет "Харківський політехнічний інститут", 2025)
The problem of determining the complex influence of a group of electricity networks (external electricity networks, built-in transformer substations, cable electric heating systems, etc.) on the magnitude of the summary magnetic field (MF) in a residential premise of a building has not been sufficiently researched. This results in an overestimation of the assess the magnitude of the summary MF, generated by the group of electricity networks, as well as to the use of technical measures to reduce this MF, which have excessive efficiency and are accompanied by excessive expenses. The goal of the work is to investigate of the complex influence of external and internal electricity networks on the MF level in residential premises of buildings and definition of conditions, which provide the minimum necessary limitations on the MF flux density of individual electricity networks, at which the summary level of MF in residential premises, does not exceed the normative level of 0.5 μT. The methodology of determining the complex influence of the group of electricity networks on the level of MF in residential premises is based on the Biot-Savart’s law and the principle of superposition and allows determining the functional dependence between the instantaneous values of currents in electricity networks, their geometrical and physical parameters, and the summary effective value of MF flux density in the premise. Scientific novelty. For the first time, the methodology for determining the complex influence of the group of external and internal electricity networks on the level of MF in residential premises is proposed. Practical significance. The implementation of the proposed methodology will allow to reduce the calculated coefficient of normalization of the MF of individual electricity networks by 25–50 %, which, in turn, will contribute to the reduction of economic costs for engineering means of normalizing the summary MF in residential premises, caused by the influence of the group of electricity networks.

Проблема визначення комплексного впливу групи електромереж (зовнішніх електромереж, вбудованих трансформаторних підстанцій, систем кабельного електрообігріву тощо) на величину сумарного магнітного поля (МП) в житловому приміщенні будинку не достатньо досліджена. Це призводить до завищеної оцінки величини сумарного МП, що створюється группою електромереж, а також до застосування технічних заходів зі зменшення цього МП, які мають надмірну ефективність і супроводжуються зайвими витратами. Метою роботи є дослідження комплексного впливу зовнішніх та внутрішніх електромереж на рівень МП в житлових приміщеннях будинків, та визначення умов, які забезпечують мінімально необхідні обмеження індукції МП окремих електромереж, за яких сумарний рівень МП в житлових приміщеннях не перевищує нормативний рівень 0,5 мкТл. Методика визначення комплексного впливу групи електромереж на рівень МП в житлових приміщеннях базується на законі Біо-Савара та принципі суперпозиції і дозволяє визначити функціональну залежність між миттєвими значеннями струмів в електромережах, їх геометричними і фізичними параметрами, та сумарним діючим значенням індукції МП в приміщенні. Наукова новизна. Вперше запропоновано методологію визначення комплексного впливу групи зовнішніх і внутрішніх електромереж на рівень МП в житлових приміщеннях. Практична значимість. Впровадження запропонованої методології дозволить зменшити розрахунковий коефіцієнт нормалізації МП окремих електромереж на 25–50 %, що, у свою чергу, сприятиме зменшенню економічних витрат на інженерні засоби нормалізації сумарного МП у житлових приміщеннях, зумовленого впливом групи електромереж.
Keywords: magnetic field of a group of electricity networks; residential premises; high-voltage overhead power line; built-in transformer substations; cable electric heating system of the floors; магнітне поле групи електромереж; житлові приміщення; високовольтні повітряні лінії електропередачі; вбудовані трансформаторні підстанції; кабельні системи електрообігріву підлог